Organogels of FmocFF: Exploring the Solvent-Dependent Gelmorphic Behavior - Basanta Saikia; Dong Chen; Yovan de Coene; Stijn Van Cleuvenbergen (Gels)
FmocFF (9-fluorenyl methoxycarbonyl-phenylalanine) is an extensively studied low-molecular-weight hydrogel. Although there have been numerous studies on FmocFF hydrogel, its potential to form organogels has not been well explored. In this work, we systematically explore the organogels of FmocFF in a wide range of organic solvents. FmocFF is found to be a robust organogeltor, and the subsequent organogels exhibit diverse gelmorphic behavior exhibiting various degrees of crystallinity and morphology depending on the solvent used. The mechanical strength of the organogels is evaluated using rheology. A novel technique, in situ SHG microscopy, is introduced to study the gel structure in its native state. In addition to the solvent–solute interactions that are typically used to predict gelmorphic behavior, we observed indications that the degree of crystallinity also plays a significant role in determining the mechanical properties and structure of FmocFF organogels.